Time‐averaged SO2 fluxes of subduction‐zone volcanoes: Example of a 32‐year exhaustive survey for Japanese volcanoes. Issue 15 (6th August 2013) - Mori, Toshiya; Shinohara, Hiroshi; Kazahaya, Kohei; Hirabayashi, Jun‐ichi; Matsushima, Takeshi; Mori, Takehiko; Ohwada, Michiko; Odai, Masanobu; Iino, Hideki; Miyashita, Makoto
Abstract : [1] All available SO2 flux data for 32 years (1975–2006) of Japanese volcanoes, accounting for about 10% of the world's arc volcanoes, were compiled to evaluate the temporal variation of the flux of each volcano and to estimate the time‐averaged SO2 flux. The compiled data revealed that 6 volcanoes (Tokachi, Asama, Aso, Sakurajima, Satsuma‐Iwojima, and Suwanosejima volcanoes) out of 17 significantly degassing volcanoes usually contributed more than 94% of the total flux. The time‐averaged annual flux was 2.2 Tg a −1, which includes intense degassing of Miyakejima volcano after 2000, which raised the figure from 1.4 Tg a −1, indicating that a single huge emitter is capable of significantly skewing regional time‐averaged degassing totals and indicating that the time‐averaged flux assessments for infrequent huge emitters are important for accurate estimation. The regional SO2 flux distribution in cumulative frequency‐flux plot does not obey a power law distribution. It shows a roll‐off curve bending at about 500 t d −1, implying that it is misleading to assume the power law distribution for estimation of the global flux. Because the contribution of the major degassing volcanoes including the six volcanoes and additional sporadically degassing volcanoes during eruptive and posteruptive periods to the total flux is more than 95%, measurement of all large flux volcanoes can approximate the global flux. Key Points: Compilation of sulfur dioxide flux of Japanese volcanoes during 1975‐2006 Time‐averaged annual sulfur dioxide flux of Japanese volcanoes is 2.2 Tg/a For the time‐averaged flux assessments, infrequent huge emitters are important